2000
DOI: 10.1002/hep.510310212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the histamine H1receptor blocker, pyrilamine, on spontaneous locomotor activity of rats with long-term portacaval anastomosis

Abstract: To find out whether the changes in the brain histaminergic system are involved in the pathophysiology of portalsystemic encephalopathy, we examined the effects of histamine H 1 receptor blockade on spontaneous locomotor activity, feeding, and circadian rhythmicity in rats with portacaval anastomosis (PCA). Pyrilamine, an H 1 receptor blocker (15 mg/kg/day), was delivered with osmotic minipumps. Spontaneous locomotor activity was recorded for 72 hours in the open-field with an electromagnetic detector. Food int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Regarding conflicting data on serotonergic control of RWA, the possible involvement of other neurotransmitters should not be ignored. For instance, the antagonizing effects of olanzapine on the histamine 1 (H 1 ) receptor might also lead to reduced physical activity and increased food intake (Fukagawa et al 1989;Lozeva et al 2000). In addition, possible antagonism of the dopamine (DA) system causing decreased motor activity should not be disregarded, although it is generally stated that olanzapine has only limited extrapyramidal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding conflicting data on serotonergic control of RWA, the possible involvement of other neurotransmitters should not be ignored. For instance, the antagonizing effects of olanzapine on the histamine 1 (H 1 ) receptor might also lead to reduced physical activity and increased food intake (Fukagawa et al 1989;Lozeva et al 2000). In addition, possible antagonism of the dopamine (DA) system causing decreased motor activity should not be disregarded, although it is generally stated that olanzapine has only limited extrapyramidal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rats with chronic PCA show a significant improvement in their circadian rhythmicity and feeding following treatment with the histamine H 1 receptor antagonist, pyrilamine (mepyramine). 8 Antihistamines have been used in patients with cirrhosis without apparent side effects. 47 Given that the most-commonly prescribed sleeping-aid drugs, the benzodiazepines, are not recommended for cirrhotic patients because they may precipitate overt encephalopathy, and in view of the fact that there are no clinical studies on the effects of melatonin in patients with cirrhosis, these findings suggest that centrally acting antihistamines may be beneficial in the treatment of the early symptoms of HE, particularly the altered sleep patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these possibilities, we have previously shown that blockade of central histamine H 1 receptors with the specific antagonist, pyrilamine (mepyramine), restores the altered circadian rhythmicity of feeding and locomotor activity. 8 Together, these findings suggest an involvement of histamine H 1 receptors in the pathophysiology of HE.Abbreviations: HE, hepatic encephalopathy; PCA, portacaval anastomosis; AP, anteroposterior.From the …”
mentioning
confidence: 95%
See 2 more Smart Citations